1987
DOI: 10.1115/1.3248038
|View full text |Cite
|
Sign up to set email alerts
|

Spectral and Total Radiation Properties of Turbulent Hydrogen/Air Diffusion Flames

Abstract: A study of the structure and radiation properties of round turbulent hydrogen/air diffusion flames is described. Measurements were made of mean and fluctuating streamwise velocity, mean temperatures, species concentrations, spectral radiation intensities, and radiant heat fluxes. The measurements were used to evaluate predictions based on the laminar flamelet concept and narrow-band radiation models both ignoring (using mean properties) and considering (using a stochastic method) effects of turbulence/radiatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
23
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
3
3
3

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(25 citation statements)
references
References 0 publications
2
23
0
Order By: Relevance
“…The computational modelling of rim-stabilised fires is mature with good agreement between the predicted and measured mean temperature and major chemical species established, Gore et al (1987) for example. This is not the case for lifted jets where computational studies have focussed on understanding the mechanism for the location of the combusting flame base and good agreement between predicted and measured flow properties The ratio of these time-scales is defined as the Damköhler number.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The computational modelling of rim-stabilised fires is mature with good agreement between the predicted and measured mean temperature and major chemical species established, Gore et al (1987) for example. This is not the case for lifted jets where computational studies have focussed on understanding the mechanism for the location of the combusting flame base and good agreement between predicted and measured flow properties The ratio of these time-scales is defined as the Damköhler number.…”
Section: Introductionmentioning
confidence: 99%
“…The details of implementation are considered further below. As jet fires have a dominant flow direction it is common for the flame structure of a rim-stabilised jet fire to be calculated in this way, Gore et al (1987). The computational advantages of a parabolic flow model over a fully elliptic solver are clear, as no iteration cycle of a pressure correction algorithm is required in its solution as the dominant flow direction has a time like quality allowing a marching procedure in the dominant flow direction.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, studies by Cox (1977), Tamanini (1977), Kabashnikov and Kmit (1979), Souil et al, (1980Souil et al, ( , 1984, Grosshandler and Joulain (1986), Fischer et al (1987), Fischer and Grosshandler (1988), as well as Faeth and his students (Jeng et al, 1984;Gore andFaeth, 1986, 1988;Gore et al, 1987aand 1987b, Kounalakis et al, 1988Gore, 1988) discussed and showed the strong coupling effects between turbulence and radiation.. A detailed discussion of studies related to turbulentradiation interactions was given by Faeth et al (1985Faeth et al ( , 1989.…”
Section: Introductionmentioning
confidence: 99%
“…The attempts to account for the effects of radiation on flow and temperature fields in a turbulent environment include those by Cox (1977), Tamanini (1977), Kabashnikov and Kmit (1979), Grosshandler and Joulain (1986), Fischer et al (1987), Fischer and Grosshandler (1988), as well as Faeth and his students (Gore andFaeth, 1986, 1988;Gore et al, 1987aand 1987b, Kounalakis et al, 1988Gore, 1988) who discussed and showed the strong coupling effects between turbulence and radiation. A detailed discussion of studies related to radiation-turbulence interactions w& given by Faeth et al (1985Faeth et al ( , 1989.…”
Section: Introductionmentioning
confidence: 99%